Identifikasi Diagnosis Gangguan Autisme Pada Anak Menggunakan Metode Modified K-Nearest Neighbor (MKNN) - Jojor Jennifer BR Sianipar; Muhammad Tanzil Furqon; Putra Pandu Adikara (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Autism is a neurological disorder that shows significant result as a lack of ability to form social relationships, normal communication, and behavior in children. This symptoms generally appear before children reach the age of 3 years. It is not classified as a psychiatric disease because autism is a disorder that occurs malfunction of children's brain and it is manifested on children's behaviour. Some research states that autism causes as the neurodevelopmental disorder that causes abnormalities in children's brain structure. Different experts mentioned that autism in children caused by the kind of food they consumed or they living environment that contain many harmful substances that shows in children's behaviour. Therefore, the system for the identification of autism disorders in children will be create to help identifies autism disorder by using the method of Modified K-Nearest Neighbor (MKNN). It is one of classification method based on the appearance of largest classes in data training. There are 14 symptoms from 4 aspects that are used as parameters in the development of the system. The output of the system is showing whether a child is autistic individuals or not. Based on the testing that has been done on the system that using Modified K-Nearest Neighbor (MKNN), maximum accuracy shows 100% accuracy while minimum accuracy is 92%. Based on those results, the uses of Modified K-Nearest Neighbor (MKNN) method can be implemented in our daily life.